Normal creatinine-kinase levels in post-COVID myositis: insights into localised muscle involvement - Hirushi S. Jayasekera; Mahmoud Elshehawy; Johnson Olarewaju; Ayman Askari (Clinical Medicine)
Introduction: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2; coronavirus 2019; COVID-19) has been increasingly implicated in post-infectious inflammatory complications, including varied presentations of inflammatory myopathies.1,2 Most literature highlights severe, systemic muscle involvement requiring immunosuppression, whereas localised myositis with normal creatine kinase (CK) levels remains underrecognised.3This case presents a rare instance of localised paraspinal and proximal thigh myositis post-COVID-19, where CK levels remained normal, despite significant muscle involvement. Method: A 41-year-old previously healthy man presented with severe diffuse back and leg pain, muscle cramps, and low-grade fever for 2 weeks after confirmed COVID-19 infection. Examination revealed proximal thigh weakness (MRC Grade 3/5) and tenderness without neurological deficits. Investigations, including blood tests, magnetic resonance imaging (MRI), computed tomography (CT), autoimmune screening, echocardiography, blood cultures and electromyography (EMG) studies. were conducted.1Management required evaluating the progression of symptoms in the light of test results to identify the aetiology of disease, considering differential diagnosis and early establishment of localised vs systemic inflammatory myopathy.2 The patient was diagnosed as post-viral myositis with a normal CK. Empirical intravenous piperacillin-tazobactam was discontinued after infection was excluded. Simple analgesia and vitamin D sufficed for symptom control. The patient showed resolution of fever, significant improvement in muscle pain and normalisation of inflammatory markers, preventing the need for immunosuppression. Results and Discussion: Laboratory findings showed elevated C-reactive protein (237 mg/L), white cell count (12.0 × 109/L), and neutrophilia (9.4 × 109/L). Alkaline phosphatase (192 U/L) and gamma glutamyl transferase (202 U/L) were mildly elevated, while CK levels were normal (22 U/L, peaking at 56 U/L). MRI revealed diffuse oedema in posterior paraspinal muscles without abscess or infection, and CT imaging confirmed intermuscular oedema in paraspinal and proximal thigh muscles without systemic involvement. Autoimmune screening (antinuclear antibodies, weakly positive; extractable nuclear antigen antibodies and anti-neutrophil cytoplasmic antibodies, negative) and echocardiogram were unremarkable. Blood cultures showed no growth and EMG displayed a myopathic pattern in the right shoulder.This case provides insight into an atypical presentation of post-COVID 19 myositis, where the CK level remains normal despite muscle weakness.3 It evaluates the diagnostic and management challenges in this scenario. Other differentials include amyopathic dermatomyositis (ADM). However, differentiating localised post-viral myositis from ADM is essential, because ADM presents with cutaneous manifestations, which are absent in this case. A detailed history of recent viral illness and advanced imaging (eg, MRI) are critical for identifying myositis and excluding systemic or infectious causes.1 Conclusion: This case highlights that post-viral localised myositis can present with significant muscle involvement despite normal CK levels, necessitating MRI for diagnosis.1,3 Early rheumatology input can optimise management by differentiating self-limiting inflammatory myopathies from those requiring immunosuppression.